Modelling & Static Analysis of Automotive Wheel Rim using different materials. Issue 1 (April 2021) - Agarwal, Sumit; Tripathi, Mehair; Dey, Prasanta; Kumar, Rohit; Awasthi, Ankita
Abstract: In this paper, we compare equivalent stress, Total deformation and equivalent elastic strain in 19-inch wheel rim of MG Gloster by Finite element method. The need of Wheel Rim is to get the stable base on which the tyre mounted. It should acquire the tyre as per the size, dimension, and shape required for the vehicle. Modelling of the rim was done by using 3-D modelling software SOLIDWORKS 2019, whereas the static structural analysis was done by using ANSYS R2 2020. ANSYS WORKBENCH R2 2020 is the software used for regular testing and simulation of materials used for the wheel rim to get the required calculations and result. ANSYS WORKBENCH R2 2020 performed the structural analysis by the material used are structural steel, carbon fiber (Low Grade), Kevlar 29, E-Glass, S-Glass, basalt, Al 6061 T6 and High Strength Low Alloy steel, their relative performances have observed respectively. The analysis is carried out for tyre inflation pressure, rotational velocity and moment condition. This analysis carried out to find the best material out of the listed materials for the wheel rim that gives optimum results for making an effective rim structure.